Making embedded software reuse practical and safe. - Leveson, Nancy G.
Reuse of application software has been limited and sometimes has led to accidents. This paper suggests some requirements for successful and safe application software reuse and demonstrates them using a case study on a real spacecraft.
Keywords: Computer systems organization; Special purpose and application based systems; Real time and embedded systems; Software; Software engineering; Requirements / Specifications; Reusable software; Design tools and techniques; Software libraries; Design; Documentation; Real time and embedded software; Software reuse